The Application of Mahagony Bark (Swietenia Mahagony L.) for Natural Dyeing - lutfi, Immas; Fatoni, Rois; Fatimah, Siti (Advance Sustainable Science, Engineering and Technology, 2020)
Recently many batik industries owner have switched to using natural dyes because synthetic dyes in the long time have a negative impact on the environment. Natural dyes that are widely used are mahogany (Swietenia Mahagony L.) bark dyes. In the process of coloring batik fabric, there is stage of fixation. Fixation is the stage of binding the color with the fixator. There are three types of fixators used, namely alum (Al2(SO4)3.12H2O), calcium oxide (CaO) and ferrous sulphate (FeSO4) with certain concentrations. The owner of batik industries don't know yet the concentration of a strong and optimal fixator for binding natural dyes in batik fabric. The purpose of this study is to determine the type of strong fixator and optimal concentration of fixator for binding natural mahogany dyes on batik fabric. The owner of batik industries usually use an estimated concentration of 30 g / L to 100 g / L. In this study, the variables are 30 g / L, 60 g / L and 90 g / L in each type of fixator to test the color aging value. and color fastness to rub wet and dry. Judging from the value of R% (color aging) and color fastness test against wet and dry rubbing, it can be concluded that alum and calcium oxide are strong fixators that used with mahogany dyes and the most optimal concentration of alum and calcium oxide is 60 g / L.Â